Tubulovillous Adenoma of Duodenum: A Case Report - Ahmed, Tanvir; Islam, Mansurul; Hassan, Mohammad Rashedul; Alam, Mohammed Shah (Journal of Shaheed Suhrawardy Medical College, 2021)
Tumors arising from the upper GIT are usually of epithelial origin and are mostly benign. Even when they do occur, they are usually considered as premalignant lesions with a risk of transformation to malignant ones.Tubulo-villous adenomas represent lesions that are histologically intermediate between tubular and villous polyps. These account for the majority of colonic polyps.We present a case of benign adenomas arising from the duodenum, an extremely rare diagnosis with an average annual incidence rate of 9.9 per million people.Among these uncommon tumors,Duodenal tumors are even rarer with average incidence rate of 0.4% only. Histopathological examination mostly shows villous type.Tubulovillous histology is extremely rare with an incidence of less than 1% of all duodenal tumors. However, these tumors are being diagnosed with increasing frequency due to more widespread use of endoscopy. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 58-60